2009
DOI: 10.1016/j.cyto.2008.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in circulating IL-8/CXCL8 isoforms in neonates

Abstract: Interleukin-8 (IL-8/CXCL8) is widely expressed in fetal tissues although inflammatory changes are not seen. Circulating IL-8 is comprised of an endothelial-derived 72 correlates with a maturational increase in the neutrophil chemotactic potency of plasma IL-8. The emergence of [ser-IL-8] 72 as the major isoform is likely due to increased plasma 77 -convertase activity and/or changes in the cellular sources of IL-8. Developmental changes in IL-8 isoforms may serve to minimize its inflammatory effects i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 30 publications
0
22
1
Order By: Relevance
“…Most recently, studies have demonstrated other unique functional features of the newborn immune system, potentially allowing age-specific interactions between innate and adaptive immune cells during the course of an infection. For example, neonatal immune cells can produce developmentally unique cytokine isoforms, and two examples have been reported in humans with IL-4 and CXCL8 (also known as interleukin-8 (IL-8) [32,33]. In addition, a large proportion of human naïve neonatal T cells are able to produce the CXCL8 chemokine upon stimulation [34].…”
Section: Box 2 Relative Importance Of the Innate And Adaptive Immune mentioning
confidence: 99%
“…Most recently, studies have demonstrated other unique functional features of the newborn immune system, potentially allowing age-specific interactions between innate and adaptive immune cells during the course of an infection. For example, neonatal immune cells can produce developmentally unique cytokine isoforms, and two examples have been reported in humans with IL-4 and CXCL8 (also known as interleukin-8 (IL-8) [32,33]. In addition, a large proportion of human naïve neonatal T cells are able to produce the CXCL8 chemokine upon stimulation [34].…”
Section: Box 2 Relative Importance Of the Innate And Adaptive Immune mentioning
confidence: 99%
“…However, several lines of evidence indicate that IL-8 and TGF-␤ may not be important as macrophage chemoattractants in the fetal intestine. In the fetus, IL-8 is comprised mainly of a longer, less-potent 77-amino acid isoform (unlike the shorter 72-amino acid isomer in the adult) (35). Similarly, TGF-␤ bioactivity is low in the early-and midgestation fetal intestine (A. Maheshwari, N. Ambalavanan, T. Nicola, D. R. Kelly, J. M. Murphy-Ullrich, M. Athar, M. Shimamura, V. Bhandari, C. Aprahamian, R. A. Dimmitt, R. Serra, and R. K. Ohls, unpublished observations).…”
mentioning
confidence: 99%
“…Furthermore, in NEC-affected tissue, IL-8, a member of the CXC chemokine family with chemotactic activity, is found in excessive amounts and has been speculated to be associated with severe inflammatory conditions (5,21). However, in the fetal intestine, IL-8 exerts other effects, stimulating maturation, but without associated inflammation (23). IL-8 also stimulates intestinal cell proliferation, differentiation, migration, protection from injury, and prevention from cell death (20,22).…”
mentioning
confidence: 99%